2013
DOI: 10.7205/milmed-d-12-00432
|View full text |Cite
|
Sign up to set email alerts
|

Cypriot and Greek Army Military Boot Cushioning: Ground Reaction Forces and Subjective Responses

Abstract: Lower limb injuries are a continual and serious issue for military personnel. Such injuries have been associated with the requirement to train in military boots (MBs) and might be offset with commercial insoles. In this study, ground reaction forces were measured in seven male participants wearing running shoes (RS), MBs commonly used by Cypriot and Greek Army personnel, and the MBs with two types of shock-absorbing insole. The participants performed 4-min trials at walking pace (5 km·h-1) and running pace (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 21 publications
6
34
1
Order By: Relevance
“…Comparing intake measurements (before gait retraining) to the literature, our results confirmed the findings by Paisis et al that stride length, cadence, and maximal vertical ground reaction forces do not differ significantly when running at 10 km/h between running shoes and military boots . In their studies, using the same treadmill, participants were running at a 5% incline; in the current study, 1% incline was used.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Comparing intake measurements (before gait retraining) to the literature, our results confirmed the findings by Paisis et al that stride length, cadence, and maximal vertical ground reaction forces do not differ significantly when running at 10 km/h between running shoes and military boots . In their studies, using the same treadmill, participants were running at a 5% incline; in the current study, 1% incline was used.…”
Section: Discussionsupporting
confidence: 90%
“…Among other factors, military boots differ from running shoes in design (shaft), weight (heavier), and sole flexibility (stiffer) . In studies comparing running in shoes versus running in military boots at 10 km/h on a treadmill, conflicting results were presented; one research group found no significant differences in stride length, cadence, and maximal vertical ground reaction forces, but in one other study running at 14.4 km/h in army boots was associated with significantly greater loading impact compared with cross‐trainer and running type shoes . The goal of conservative treatment of ERLP in military patients is to help them return to military duties, including running in boots, without re‐injury.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were recreational runners who trained at least threeD 3 1 times per week and had a minimum of three years of running experience. The sample size was selected on the basis of previous work investigating the mechanics of running in military footwear (Nunns et al, 2012;Paisis et al, 2013;Sinclair, Hobbs, Taylor, Currigan, & GreenhalghD 3 2 , 2014). All participants were right-D 3 3 foot dominant and considered to exhibit a rearfoot strike pattern as they demonstrated a clear first peak in their vertical ground reaction force time-curve (Cavanagh & Lafortune, 1980).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Military boots have frequently been implicated as a potential mechanism behind the high incidence of injuries among military recruits 10. Poor shock absorption characteristics have been identified in military boots when compared with running shoes 11.…”
Section: Introductionmentioning
confidence: 99%